Identification of subgroups among fibromyalgia patients - D. Chaleil; B. Auvinet (PAGEPress Publications, 2012)
This paper presents some hypotheses concerning the identification of homogeneous subgroups among fibromyalgia (FM) patients in order to improve the management of the disease. It also reviews the available literature about this subject. Three methods for subgrouping are discussed according to clinical features, biomarkers, and gait analysis. Clinical subgrouping based on cluster analysis has been used for the identification of homogeneous subgroups of patients and, more recently, homogeneous clinical features. So far, longitudinal studies using clinical subgroups to direct treatment and predict outcome are still required. Biomarkers in FM, which is a neurobiological disease, are of promising interest, nevertheless currently, none of them can be used to subgroup FM patients. Due to the fact that cortical and subcortical mechanisms of gait control share some cognitive functions which are involved in FM, gait markers have been proposed to evaluate and to subgroup FM patients, in clinical settings. Three out of 4 core FM symptoms are linked to gait markers. Kinesia measured by means of cranio-caudal power is correlated to pain, and could be proposed to assess pain behavior (kinesiophobia). Stride frequency, which is linked to physical component, allows the identification of a hyperkinetic subgroup. Moreover, SF has been correlated to fatigue during the 6 minute walking test. Stride regularity, which expresses the unsteadiness of gait, is correlated to cognitive dysfunction in FM. Decreased stride regularity allows the recognition of a homogeneous subgroup characterized by an increased anxiety and depression, and decreased cognitive functions. These results need further studies to be validated and so used in the daily clinical practice.